2017
DOI: 10.1097/md.0000000000009171
|View full text |Cite
|
Sign up to set email alerts
|

The application of 18F-FDG PET/CT in ovarian immature teratomas when pathological examination results contradict clinical observations

Abstract: Rationale:Fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) could reveal potential lymph node involvement and assisted locating sample sites for pathological examinations.Patient concerns:Help choose the right treatment strategies for patients. To better stage immature ovarian teratomas with 18F-FDG PET/CT when lymphatic metastasis is suspected while lymph node biopsy results are negative.Diagnoses:The ultimate pathological diagnosis was left ovarian cancer, an im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…FDG-PET/CT is widely used for cancer staging and surveillance. FDG-avid lymph nodes, however, are not specific for malignancy [ 19 ]. Inflammatory cells avidly take up FDG when undergoing the energy-dependent process of activation.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET/CT is widely used for cancer staging and surveillance. FDG-avid lymph nodes, however, are not specific for malignancy [ 19 ]. Inflammatory cells avidly take up FDG when undergoing the energy-dependent process of activation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 3 ] However, elevated serum CA 19-9 has also been observed for some patients with either benign or malignant dermoid cysts. [ 4 – 9 ] It has also been reported that CA 19-9 staining is prominently noted around the apical cytoplasma of the epithelial lining. This phenomenon has led Atabekoglu et al to suggest that CA 19-9 is secreted into the cystic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Foci of punctate fatty tissue and scattered calcifications in a solid ovarian mass on CT scan discriminate IT from MT (Figure 1). The combination of positron emission tomography (PET) and CT gives the additional benefit of providing morphologic and functional details in the case of IT [11].…”
Section: Review Clinical and Radiological Featuresmentioning
confidence: 99%
“…The combination of positron emission tomography (PET) and CT gives the additional benefit of providing morphologic and functional details in the case of IT [ 11 ].…”
Section: Reviewmentioning
confidence: 99%